THE ROLE OF INSTRUMENTAL MOTIVATION AMONG EFL STUDENTS IN LANGUAGE LEARNING PROCESS - Nanda Aspuri; Iskandar Abdul Samad; Siti Sarah Fitriani; Nanda Marlina Abdul Samad (Universitas Sembilanbelas November Kolaka, 2019)
The aim of this study was to find out the role of instrumental motivation in the English learning process of English as a Foreign Language (EFL) students. Motivation can be described as a process to influence someone or many people to do the desired work, in accordance with certain goals set in advance. For EFL student, motivation was required to achieve success in the process of learning English. Based on the previous study, kind of motivation, called Instrumental motivation, has an important role in English learning process. The participants of the study were 10 EFL students; 5 students were from post-graduate program of English Department of Syiah Kuala University and 5 students were from undergraduate program of English Department of UIN Ar-Raniry. This qualitative study applied interview to gather data. The result of the study revealed that the participants have a strong instrumental motivation involved in their English learning process. Considering the results of this study, everyone, whether parents and teachers need to motivate their children and their EFL students by motivating them instrumentally in the process of learning and teaching English.